Antibiotic Susceptibility Patterns and Extended Spectrum Beta-Lactamase (ESBL) production in Enterobactericeae Isolated from Stool Samples of HIV and AIDS Patients in Ibadan, Nigeria - Falodun, Olutayo Israel; Ajayi, Olayemi; Ademola, Adewuyi Ebenezer; Bakarey, Solomon Adeleye (Janaki Medical College Journal of Medical Science, 2021)
Background and Objectives: Abuse and indiscriminate use of antibiotics, prolong hospital admission, travel history, organ transplants, immunocompromised conditions and age are parts of the factors that contribute to development of antibiotic resistance and intestinal carriage of Extended Spectrum Beta-Lactamases (ESBL) Enterobacteriaceae. These bacteria affect the course and outcome of an infection and continue to pose a challenge to infection management worldwide. This study was carried out to determine the antimicrobial susceptibility patterns and prevalence of ESBL-producing Enterobacteriaceae isolated from stool samples of HIV and AIDS patients in Ibadan, Nigeria. Materials and Methods: One hundred stool samples were collected from consenting HIV and AIDS patients accessing care in Antiretroviral (ARV) Clinic in a secondary and a tertiary health care facility in Ibadan, Nigeria. Gram-negative bacteria were isolated and identified using conventional methods. Antimicrobial susceptibility test was carried out using the Kirby Bauer disc diffusion technique. Phenotypic detection of ESBL-producing isolates was carried out using Double Disc Synergy Test (DDST). Results: A total of 240 Gram-negative bacteria were isolated comprising 100 (41.6%) Escherichia coli, 33(13.8%) Klebsiella pneumonia, 27(11.3%) Serratia marcescens, 20(8.3%) Salmonella enterica, 9(3.8%) Proteus vulgaris, 13(5.4%) Proteus mirabilis, 21(8.8%) Citrobacter freundii and 17(7.1%) Enterobacter aerogenes. Out these, 56 (23.3%) were ESBL-producers; comprising 23(41.0%) Escherichia coli, 9(16.0%) Klebsiella pneumonia, 6(10.7%) Serratia marcescens, 5(8.9%) Salmonella enterica, 3(5.3%) Proteus vulgaris, 5(8.9%) Proteus mirabilis, 2(3.6%) Citrobacter freundii and 3(5.4%) Enterobacter aerogenes. Among the ESBL producers, 45 (80.3%) and 38 (67.8%) showed resistance to trimethoprim/sulfamethoxazole and aztreonam while 3 (3.5%) showed resistance to ertapenem. Also, 96.4% (54/56) of the ESBL producers were multidrug resistant. Conclusion: This study showed that HIV and AIDS patients are reservoirs of ESBL-producing Enterobacteriaceae through faecal carriage, presenting them as likely source of dissemination of ESBL producer in community and hospital settings.